An interview with Dr. Rashid Ghannouchi - Malik, Maszlee (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Rashid Ghannouchi is the co-founder of the Ennahda Movement (Party) of Tuni- sia, currently the largest political party and part of the country‟s troika ruling coalition. Born in the year 1941, Ghannouchi is globally acknowledged as the party‟s “intellectual leader” and ideologue. He is considered as one of the world‟s leading figures in the area of contemporary Islamic thought. His ideas on the issues of Islam and modernity, democracy and secularism, relations between East and West, among Muslim Women in human rights and civil society have been quoted by Islamists, Muslim intellectuals and activists around the world. He was awarded the Chatham House Prize in 2012 by Prince Andrew, Duke of York, alongside Tunisian president, Moncef Marzouki, for “the successful compromises each achieved during Tunisia‟s democratic transition.”